Keseimbangan Hak dan Kewajiban Para Pihak dalam Hukum Kontrak - Faiqa Syifa Irawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The balance of rights and obligations in contracts is a fundamental basis for creating justice and legal certainty. With effective protection for all parties in the contract, be it in the realm of commerce or other social relations, it is expected to create a conducive legal environment, which in turn encourages social and economic development. The process of drafting contracts in various fields, such as micro, small and medium enterprises (MSMEs), shows the importance of good design to guarantee the rights of each party In this context, it is important to explore how the contract structure can be designed in such a way that both parties can fulfill their rights and obligations fairly, as well as serve as a guideline in resolving disputes that may arise in the future. rights and obligations are basic principles in contract law that aim to create justice, legal certainty, and balanced protection for all parties to the agreement. In the process of contract formation, balance is achieved through the principles of freedom of contract, good faith, and transparent negotiations so that the rights and obligations of both parties are arranged fairly and proportionally.